MODERN PRESCHOOL EDUCATION: A PATH IS FROM TRADITIONS TO INNOVATIONS - Nelly Lysenko (Vasyl Stefanyk Precarpathian National University, 2018)
The urgency of modern approaches to pro-ecological education determines the present state of the natural environment. Traditionally it is considered in the context of the tasks of familiarizing children with nature. The fundamentals of the ecological orientation of the content of knowledge about living and inanimate nature are laid down in the writings of famous teachers - representatives of European educational systems: Ya.A. Komenskyi, F. Frebel, S. Frenet, as well as followers of their ideas in Ukraine: S. Rusova, V. Sukhomlynskyi, K. Ushynskyi and others. Based on the scientific approaches of biologists, ecologists, and environmentalists for preschoolers, there are recommended knowledge that is accessible to their perception. These knowledges are about the atmosphere, soils, water, plants and animals, etc. including the processes that take place. Accordingly, the natural environment appears to the preschool child as a holistic and indivisible with which the person interacts, knows and protects. Nature is its habitation, food, clothing, inspiration for creativity and activity. The disastrous effect on plants, animals, lakes and rivers limits the positive and objective view in the future.Accordingly, a pro-ecological education should be started from the earliest years for the purpose of every child will master not only knowledge of nature, but also practical skills of its protection.The content of pro-ecological education is quite multifaceted and versatile, so children are defined it as knowledge of the world in which they live; about the air they breathe; about the food they eat; about the environment of adults and peers with whom they communicate; about the lifestyle of their family and household.Modern educational technologies provide the inseparable unity between the scientific knowledge and the educational goals they implement. Accordingly, they are in a position to change the style and quality of life of children and their parents. Pro-ecological education is based on the scientific basis of the organization of its leadership in pre-school establishments and on the principles of preschool didactics. Its content can be realized in various forms.The article presents an example of the organization of green preschool in the Republic of Poland in the channel of initiatives of International Foundation of Nature Supporters "Children and Nature Network". The practice of a green (forest) kindergarten aims at maximum engagement of children to use the design methods of search and research activity in the knowledge of the natural environment. Such methods are intended to provide children with a wide range of information as the basis of their pro-ecological education. The experience of colleagues from the Republic of Poland encourages theorists and practitioners of pre-school education to active seek of forms of cooperation. Key words: nature, environment, ecological education, active forms of education, "green (forest) kindergarten".